A more universal and stable method for lactate dehydrogenase isoenzyme test. Issue 32 (30th July 2019) - Li, Peijuan; Qiu, Nanhai; Zhang, Li; Zhong, Guishu; Zeng, Fancai
Abstract : As an important enzyme for energy metabolism, lactate dehydrogenase (LDH) and its isoenzymes (LDH isoenzymes) have been extensively studied. Abstract : As an important enzyme for energy metabolism, lactate dehydrogenase (LDH) and its isoenzymes (LDH isoenzymes) have been extensively studied. LDH zymography is a common method to detect LDH isoenzymes, which offers the special advantage of directly observing 5 isozyme bands in the active state. But it has poor stability, and is difficult to apply for a variety of studies, so it has not been widely utilized. Here we have explored the influence of key factors including the temperature and pH of the running buffer, buffer type, and extraction methods on the detection of LDH isoforms and established a more practical and universal LDH zymography method, which can guarantee a stable and quality result, and be easily applied for different studies.